Racial and Gender Diversity of Physicians Accepted to American Military Orthopaedic and Surgical Residencies: An 18-Year Analysis. Issue 1 (10th January 2023) - Hoyt, Benjamin W.; Anderson, Ashley B.; Dingle, Marvin E.; Dickens, Jon F.; Eckel, Tobin T.; Sterbis, Joseph R.; Potter, Benjamin K.; Kilcoyne, Kelly G.
Abstract : Introduction: Orthopaedic surgery ranks among the least racially and gender diverse medical/surgical specialties. United States military surgeons train in military or military-funded residency positions to care for a markedly diverse population; however, the composition and diversity of these training programs have not been previously assessed. The purpose of this study was to analyze the trends of physician diversity in military orthopaedics in comparison with other surgical specialties over time. Methods: We performed a retrospective cohort study evaluating matriculation into first year of residency training in US military surgical training programs between 2002 and 2020. In total, 9, 124 applicants were reviewed. We collected matriculant self-reported race/ethnicity and sex and the medical/specialty program. We considered under-represented minorities as those who reported their race as African American, Indian/Alaskan Native, and Native, other, or who reported ethnicity as Hispanic. We calculated changes in persons accepted to training positions over time and used linear regression to model trends in diversity among orthopaedic matriculating residents when compared with other surgical subspecialities over time. Results: Across all surgical subspecialities, the average change in percent women was 0.94% per year for the study period (p < 0.01). The average annual percent women entering orthopaedic surgery residency programs was 14% for the 18-year study period. Across all surgical subspecialties, the average change for accepted applicants from groups underrepresented in medicine ( URiM ) was 1.01% per year for the study period (p < 0.01). The average annual percent URiM entering orthopaedic surgery residency programs was 17% for the 18-year study period. The annual change of women and URiM entering military orthopaedic residencies was 0.10% and 1.52%, respectively. Conclusions: Despite statistically significant improvements, recruitment efforts as used to date fall far short of reversing sexual, racial, and ethnic disparities in military orthopaedic residencies. Orthopaedics has a lower representation of both women and physicians with minority backgrounds when compared with many surgical subspecialties. Additional interventions are still necessary to increase diversity for military orthopaedic surgeons.